Heat Transfer Enhancement on Geothermal Energy Extraction from Unused Oil Well - Nguan, Heng Kok (IRC, 2017)
Geothermal energy is an important emerging renewable technology that has the potential to provide power from a virtually unlimited reserve worldwide. The downside to exploiting geothermal energy is the capital intensive drilling of the borehole needed to access relatively hot resources located deep under the ground. Abandoned petroleum wells present an interesting opportunity to circumvent the capital costs associated with drilling. This thesis proposes a computational model of heat transfer that is capable to closely simulate the heat flow through a double pipe heat extractor and the surrounding rock mass. Although there are already research on the power production of abandoned oil wells using numerical solution. Most of these project is focused on how to improve the efficiency by increasing heat transfer between surrounding rock mass and heat extractor via addition of insulation and types of working fluid. Therefore it is of interest to investigate enhancement of heat transfer by design modification of heat extractor via addition of swirling steel. This study will be carried out by utilizing Computational Fluid Dynamics (CFD) approach. The model will be developed to provide an accurate and realistic representation of heat flow and temperature distribution for a heat extractor retrofitted to an abandoned well. The results obtained from this research will determine if addition of swirling steel will increase the heat transfer between rock and heat extractor. This study will also provide guidance for future research on the effect of addition of swirling steel in annulus of heat extractor.